(Un)homely Dwellings: The Usher House and the Collyer Mansion - Theodora Tsimpouki (European Journal of American Studies)
In this paper, I analyze E. L. Doctorow’s 2009 novel, Homer & Langley, through the lens of Edgar Allan Poe’s short story “The Fall of the House of Usher.” While there has been a recurring claim about the significant similarities of Doctorow’s work to some of the tales by Edgar Allan Poe, there has been no critical reading that draws the connection between this novel and Poe’s famous tale. Doctorow deftly manipulates Poe’s favorite gothic connection between architectural construction and the psychological experience of characters to explore notions of home and domesticity in an increasingly urban America through a reconfiguration of the legendary Homer and Langley Collyer. In Doctorow’s novel, the Collyer brothers are not the obsessed hoarders or the models of American consumerism par excellence, as the urban myth describes them. On the contrary, they become paradigms of dwelling with alertness in the Heideggerian sense, the embodiment of an escapist mentality in a culture driven by mundane prosperity and social compliance.